Creating multilayer-structured polystyrene composites for enhanced fire safety and electromagnetic shielding. (1st August 2022) - Gao, Caiqin; Shi, Yongqian; Huang, Ruizhe; Feng, Yuezhan; Chen, Yajun; Zhu, Shicheng; Lv, Yuancai; Shui, Wei; Chen, Zhixin
Abstract: Two-dimensional (2D) titanium carbide (Ti3 C2 Tx ) with high electrical conductivity and large active surfaces has attracted extensive attention in recent years. Here, in order to address the fire safety and poor electromagnetic shielding performance of polystyrene (PS), a highly effective cetyltrimethyl ammonium bromide-multi-wall carbon nanotubes@Ti3 C2 Tx (C-MWCNT@Ti3 C2 Tx ) bilayer was deposited on PS sphere to achieve PS@C-MWCNT@Ti3 C2 Tx (PCT) composites for improving its fire safety and electromagnetic shielding performances. In addition, Ti3 C2 Tx and γ-propyl-trimethoxysilane (KH550) were adopted to modify silicon wrapped ammonium polyphosphate (SiAPP-NH2 @Ti3 C2 Tx ) via the microencapsulation strategy. Finally, the SiAPP-NH2 @Ti3 C2 Tx was incorporated into PCT composites to fabricate excellent fire-resistant PS composites, i.e. PCTS. The obtained results demonstrated that Ti3 C2 Tx not only promoted the thermal stability and fire safety but also enhanced the electromagnetic shielding performance of PS. For instance, the PS composite with three number of C-MWCNT@Ti3 C2 Tx bilayers (PCTS3) exhibited dramatically lowest the peak of heat release rate (528 kW/m 2 ) and highest electromagnetic shielding effectiveness value (11 dB), indicative of the excellent flame retardant and considerable electromagnetic shielding properties. This work sheds light on the design of multifunctional multi-layer structured polymer composites. Graphical abstract: Image 1